2008
DOI: 10.1007/s12043-008-0050-z
|View full text |Cite
|
Sign up to set email alerts
|

Re-dispersible Li+ and Eu3+ co-doped CdS nanoparticles: Luminescence studies

Abstract: Re-dispersible CdS, 5 at.% Eu 3+ -doped CdS, 2 at.% Li + and 5 at.% Eu 3+ co-doped CdS nanoparticles in organic solvent are prepared by urea hydrolysis in ethylene glycol medium at a low temperature of 170 • C. CdS nanoparticles have spherical shape with a diameter of ∼80 nm. The asymmetric ratio (A21) of the integrated intensities of the electrical dipole transition to the magnetic dipole transition for 5 at.% Eu 3+ -doped CdS is found to be 3.8 and this ratio is significantly decreased for 2 at.% Li + and 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The spectrum consists of many sharp peaks at 274, 312, 352, 368, and 378 nm. The peak at 274 nm corresponds to the 8 S 7/2 Ǟ 6 I 11/2 transition of Gd 3+ , [31] and this peak has the highest absorption relative to the others. It indicates the occurrence of an energytransfer process from the Gd 3+ to the Tb 3+ ion.…”
Section: Ir and Morphology Studiesmentioning
confidence: 98%
“…The spectrum consists of many sharp peaks at 274, 312, 352, 368, and 378 nm. The peak at 274 nm corresponds to the 8 S 7/2 Ǟ 6 I 11/2 transition of Gd 3+ , [31] and this peak has the highest absorption relative to the others. It indicates the occurrence of an energytransfer process from the Gd 3+ to the Tb 3+ ion.…”
Section: Ir and Morphology Studiesmentioning
confidence: 98%
“…Among these methods, co-precipitation approach is an economical and promising ways in the production of fine particles [9]. In our previous studies on luminescence properties of semiconducting oxides and sulphides, it was reported that ethylene glycol could be used as medium as well as capping agent in order to decrease agglomeration among nanoparticles [10][11][12][13]. In this paper we use ethylene glycol as medium as well as capping agent and urea is used for the precipitating agent for the preparation of NiFe 2 O 4 nanoparticles since it can produce NH 4 OH after thermal decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Ethylene glycol (EG) has peaks at 3212-3495 (broad), 2875, 2939, 1651, 1426, 1051 and 879 cm −1 . A broad peak at 3212-3495 cm −1 is due to the presence of hydrogen bonding among EG molecules (H-O· · ·H-O-) [57][58][59][60][61]. However, stretching frequency of free O-H is at 3650 cm −1 [60].…”
Section: Resultsmentioning
confidence: 99%